Moments of meeting in psychoanalysis : interaction and change in the therapeutic encounter - Lord, Susan (Relational perspectives book series, 2018)
There are moments of connection between analysts and patients during any therapeutic encounter upon which the therapy can turn. Moments of Meeting in Psychoanalysis explores how analysts and therapists can experience these moments of meeting, shows how this interaction can become an enlivening and creative process, and seeks to recognise how it can change both the analyst and patient in profound and fundamental ways.